A Deformable Motor Driven by Dielectric Elastomer Actuators and Flexible Mechanisms - Minaminosono, Ayato; Shigemune, Hiroki; Okuno, Yuto; Katsumata, Tsubasa; Hosoya, Naoki; Maeda, Shingo (Frontiers in Robotics and AI, 2019)
Soft robots with dynamic motion could be used in a variety of applications involving the handling of fragile materials. Rotational motors are often used as actuators to provide functions for robots (e.g., vibration, locomotion, and suction). To broaden the applications of soft robots, it will be necessary to develop a rotational motor that does not prevent robots from undergoing deformation. In this study, we developed a deformable motor based on dielectric elastomer actuators (DEAs) that is lightweight, consumes little energy, and does not generate a magnetic field. We tested the new motor in two experiments. First, we showed that internal stress changes in the DEAs were transmitted to the mechanism that rotates the motor. Second, we demonstrated that the deformable motor rotated even when it was deformed by an external force. In particular, the rotational performance did not decrease when an external force was applied to deform the motor into an elliptical shape. Our motor opens the door to applications of rotational motion to soft robots.